Applying the Dynamic Dual Pathway Model of Approach Coping to Collective Action Among Advantaged Group Allies and Disadvantaged Group Members - Radke, Helena R. M.; Kutlaca, Maja; Becker, Julia C. (Frontiers in Psychology, 2022)
We apply the dynamic dual pathway model of approach coping to understanding the predictors of future collective action among a sample of advantaged group allies and disadvantaged group members who were attending a protest. We propose that problem-focused approach coping (i.e., group efficacy beliefs) would be a stronger predictor of future collective action among disadvantaged compared to advantaged group members, and emotion-focused approach coping (i.e., group-based anger) would be a stronger predictor of future collective action among advantaged compared to disadvantaged group members. Data was collected from LGBTIQ+ and heterosexual people (N = 189) protesting as part of the 2019 Christopher Street Day Parade in Cologne, Germany. We found that increased group efficacy predicted intentions to engage in future collective action for the rights of sexual minorities among LGBTIQ+ but not heterosexual participants. Increased group-based anger was a predictor of future collective action intentions regardless of which group the participants belonged to. Our findings extend the dynamic dual pathway model by applying it to a sample of advantaged group allies and disadvantaged group members attending a protest using a multiple perspectives approach.